Cannabis Use and Psychosis: Theme Introduction - Martinotti, Giovanni; Di Iorio, Giuseppe; Sepede, Gianna; De Berardis, Domenico; De Risio, Luisa; Di Giannantonio, Massimo (Current Pharmaceutical Design, 2012)
Cannabis is among the most widely used illicit substances. Epidemiological and neuroscientific evidence, though poorly integrated, have established a strong association between cannabis use and increased risk of psychosis. Chronic cannabis use, especially of new synthetic varieties, may trigger psychosis and precipitate schizophrenia in vulnerable individuals. However, the specific pathways by which cannabis affects brain function are unclear. It seems likely that a complex genetic-environmental interaction may underlie the link between cannabis exposure and psychosis onset, with multiple genetic variations and several environmental factors (i.e., trauma or maltreatment during childhood) involved. Also, the possible role of basic symptoms in cannabis users is still not fully acknowledged. Basic symptoms may possibly be a marker for the development of full schizophrenia in cannabis users and their recognition may play a role in prevention strategies. Moreover, the differential impact of different types of cannabis has been generally overlooked and little is known about possible pharmacological treatment approaches (with antipsychotics, cannabis agonists, cannabis antagonists) for cannabis users at risk of psychosis. The aim of the present review is to open this issue with a broad introduction on the clinical and pathophysiological link between cannabis abuse and psychosis onset.
Keywords: Cannabis